CUSTOMER-ORIENTED APPROACH IN BRAND FORMATION AND ADVERTISING MANAGEMENT ACTIVITIES OF THE ENTERPRISE - ANDRUSHKEVYCH, Zinayida; BOIKO, Ruslan; NIANKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the advantages of using a client-oriented approach as the basis of brand formation. The relevance of the researched topic in modern economic conditions is indicated. he works of scientists engaged in the research of these issues were analyzed, insufficiently researched aspects were singled out, and an own definition of customer orientation was proposed.Characteristic features of a client-oriented approach in the formation of the company's brand have been formed. It was determined that the effective implementation of a client-oriented management approach in the enterprise should be based on the following components: client-oriented product (service); client-oriented staff; client-oriented rules and standards; client-oriented service and processes.The methods by which you can determine and evaluate the level of customer loyalty are considered, the method of determining the NPS index - Net Promoter Score (net index of promoters) is considered in detail.It is substantiated that the implementation of a client-oriented approach to the management of the company's activities can provide the following advantages: increase customer loyalty; increase the frequency of purchases; reduce complaints and refusals to purchase goods (services); create unique competitive advantages of the enterprise on the market; to receive additional income from the sale of goods, provision of services.The following conclusions were drawn: comprehensive implementation of a client-oriented approach makes it possible to increase the customer loyalty index, contributes to increasing competitiveness, and improves the image of the enterprise on the market; the technologicalization of a client-oriented approach involves the implementation of special software (CRM - Customer Relationship Management) and technical support for more effective management of relationships with clients; a client-oriented approach is an integral element of the company's brand formation and should be a component of the company's advertising policy.
Keywords: customer orientation; brand; advertising activity; consumer loyalty management